The effect of SAQ training to increase the agility of badminton atheletes aged 12-13 years - Marom, Muhammad Faisal; Darmawan, Arief; Fitriady, Gema (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
This study aims to determine the effect of the SAQ training program on increasing the agility of PB badminton athletes. Bendo Sport aged 13-15 years. The athlete sampling technique used was a total sampling of 15 male athletes. The research instrument that researchers used in this study was the Illinois Agility Test. The research method used by researchers is one group pretest-post test design. The results of calculating the data from the pretest and posttest obtained the following results, the mean pretest was 17.44 ± 0.59 and the post test was 16.34 ± 0.52. In subsequent calculations, a significance value of <0.001 was obtained. It could be concluded that there were differences before training and after training.